Digital-Based Zakat Management at the National Amil Zakat Agency - Alfiatun Zahrah; Bunga Andini; Suci Mardiyah; Syafnur Muhammad Riski; Iskandar Iskandar (General Multidisciplinary Research Journal, 2025)
Introduction:This study aims to analyze zakat management at the National Zakat Agency (BAZNAS) in the digital era, focusing on the role of information technology in improving the effectiveness, efficiency, transparency, and accountability of zakat management. As one of the pillars of Islam, zakat plays a crucial role in promoting social welfare and reducing economic inequality. Therefore, optimal zakat management is essential, especially in today’s digital environment. Methods:This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews and document analysis conducted at several zakat management institutions. The study focuses on identifying how digital systems are implemented and the challenges faced in integrating information technology into zakat management. Results:The findings reveal that the integration of digital technology—such as online platforms, mobile applications, and integrated information systems—significantly contributes to the efficiency of zakat collection and distribution processes. Digital tools also facilitate the identification of mustahik (zakat recipients), accelerate the distribution of aid, and enhance public trust in zakat institutions through transparent financial reporting. Conclusion and Suggestion: The study concludes that digital transformation plays a pivotal role in improving the performance and accountability of zakat management. However, challenges remain, including limited digital infrastructure and the need to enhance technological literacy among zakat managers. Therefore, developing robust information systems, strengthening human resource capacity, and fostering collaboration among stakeholders are key strategies for realizing effective and impactful zakat management in the digital era.